4n-6=94

Simple and best practice solution for 4n-6=94 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4n-6=94 equation:


Simplifying
4n + -6 = 94

Reorder the terms:
-6 + 4n = 94

Solving
-6 + 4n = 94

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 4n = 94 + 6

Combine like terms: -6 + 6 = 0
0 + 4n = 94 + 6
4n = 94 + 6

Combine like terms: 94 + 6 = 100
4n = 100

Divide each side by '4'.
n = 25

Simplifying
n = 25

See similar equations:

| x/4=3/4 | | 5x(2x+3)-2x(2x-1)= | | 2x-1/5=1 | | h=-16t^2+60t+2 | | 3a+6b+2a-5b= | | 2/7(x-4)=2 | | 2.20=12.15 | | 7x+2y-5x-5y= | | (5-2x)*(4-x)-2x*(x+6)=1-x | | 7(3x-5y)-4(4x-5y)= | | 6y+11=4 | | -5/7x7/4 | | 10(x-1)=10 | | -7x-10+4x=20 | | 3(y+1)=0 | | 3h-h=18 | | (3x+5)(2x+7)=22 | | (-4x^8/2x^2)^3 | | -7d=-5d+14 | | -6-7x=-27 | | 2z-8=0 | | -4z-200/12=-19 | | 2y=-2x-3 | | -4z-200/12=-10 | | 7(3x-5y)-4x(4x-5y)= | | 6u-4u=6 | | 36=9(p-1) | | 4x+5(6x+5)=-3-4(5x-7) | | 2y=-2y-3 | | 9t=12+11t | | 1/(e^x)=0 | | 10+6x-7x=8 |

Equations solver categories